Pengaruh Insentif Terhadap Prestasi Kerja Karyawan Housekeeping Pada Hotel Furaya Pekanbaru - maryantina, maryantina (Jurnal Daya Saing, 2016)
Hotel Furaya need to improve the quality of human resources in providing services to consumers. Seeing the importance of the position of human resources at the Hotel Furaya, it may be reasonable for management to give more attention through the wisdom of wisdom taken. Through research by using descriptive statistics and distributing questionnaires to 218 employees are aware that there is a significant relationship between the incentive and employee performance Housekeeping at Hotel Furaya Pekanbaru, then H0 is rejected Ha accepted Under the policy further motivate employees to work better for career advancement in the future. Keywords: employee job performance and Incentives